Zenglibao : an internet money market fund run by Tianhong Asset Management Co., Ltd. - McFarlan, F. Warren (SAGE knowledge. Cases., 2016)
Tianhong Asset Management Co. issued its first quarter report on April 18, 2014. The report announced that the shares of its Tianhong Zenglibao Money Market Fund (Zenglibao Fund) were owned by 81 million individual investors and the value of these shares exceeded 541.3 billion Yuan; the profit in the first quarter was 5.7 billion Yuan. This book profiles the the Zenglibao Fund, well-known for its associated internet asset management platform Yu'ebao.